RELATIONSHIP AMONG METAMORPHIC GRADE, VESUVIANITE "ROD POLYTYPISM" AND VESUVIANITE COMPOSITION - Gnos E.; Armbruster T. (My University, 2006)
Single-crystal X-ray study of different vesuvianite samples of known origin shows that different metamorphic grade results in different arrangements of structural rods oriented parallel to the vesuvianite c axis, interpreted as "rod polytypism." There is a systematic dependence of space-group symmetry and rod arrangement on crystallization temperature: P4nc-dominant < 300 °C, P4/n-dominant ~300-500 °C, and P4/nnc > 500 °C. Partial occupancy of the T sites (B, Al, Fe3+) and increased F-content seem to stabilize rod disorder causing P4/nnc space-group symmetry. All studied vesuvianites in calcsilicate rocks and marbles from regional- and contact-metamorphic upper amphibolite facies have disordered rods (P4/nnc symmetry). Electron-microprobe analyses of metamorphic vesuvianites from alpine and non-alpine occurrences, supported by structural investigation, showed that in addition to homo- and heterovalent substitution, partial occupancy of the commonly vacant T sites by B, Al, or Fe3+, and the (O4H4)4-1 → SiO44- (hydrogarnet-type) substitutions are significant in nature. With few exceptions, T-site occupancy seems to be restricted to high-grade metamorphic rocks whereas the "hydrovesuvianite" substitution is only found in vesuvianites formed at very low metamorphic grade. The cell parameters of vesuvianite with empty T sites increase with increasing Ti + Mg → 2 Al substitution, and this increase is even more pronounced with increasing "hydrovesuvianite" component. An increase in boron on T sites leads to a decrease of c but an increase in a. Fluorine incorporation and T-site substitution (B, Al, Fe3+) in vesuvianite are coupled with a decrease in hydroxyl groups. This causes vesuvianites to be stable under higher Xco2 conditions, and in an assemblage with quartz at conditions above the experimentally determined upper stability of quartz + T site vacant, F-free vesuvianite. Optically anomalous vesuvianites have ordered rods and are generally characterized by an intergrowth of P4/n and P4nc domains. In addition to B-rich vesuvianite and wiluite, P4nc-dominant vesuvianites are also commonly optically positive.
Keywords: ANALYSIS; CHEMICAL (VESUVIANITE); CRYSTAL STRUCTURE; METAMORPHIC PETROLOGY; POLYTYPISM